Wearable Resistance Technology to Enhance Swimming Performance - Quirke, Ellen Elizabeth (Auckland University of Technology, 2019)
Resistance training that replicates specific sport actions may optimise the transference of muscular adaptations to performance. In swimming, there are many different in-water training aids that are used by swimmers with this principle of specificity in mind. However, the majority of these have negative consequences on stroke mechanisms and technique. Wearable resistance technology (WRT) may provide a novel way to effectively overcome these challenges. It may also help improve performance when used to prime athletes. To date, physiological and performance effects of WRT use in swimming has not been reported in the literature. Therefore, the aim of this thesis was to determine: 1) the acute effects of WRT on physiological responses during submaximal freestyle swimming; and 2) whether WRT can improve 200m freestyle performance when incorporated as a post-activation potentiation (PAP) tool during a swim-specific priming strategy. Study 1 investigated the physiological response to proximal upper arm loads of 0g-500g per arm utilising WRT during submaximal 200m freestyle swimming. 15 national level swimmers (age: 16-24y, 7 male & 8 female, 200m PB: 126.31 +/- 10.46sec) completed a 7x200m incremental step test to determine submaximal swimming speed. 24 hours later six submaximal 200m freestyle swims were completed with varying wearable resistance (WR) loads (0g, 100g, 200g, 300g, 400g and 500g, randomly assigned). During the 400g & 500g trials the males showed an increase in blood lactate (BL) (400g: ↑0.74 +/- 1.32 mmol-1; ES: 0.41, 90%CI: (-0.13 – 0.96), 500g: ↑2.40 +/- 3.06mmol-1, 1.29, (-0.06-2.63)) while maintaining their submaximal speed. Conversely in females, BL was unaffected, and swimmers were unable to maintain their 200m submaximal speed (400g: ↑3.11 +/- 2.56sec; ↑1.9%, (90% CI) = 0.8-3.1, 500g: ↑4.05 +/- 2.35sec; ↑2.6%, (1.4-3.8)). Rate of perceived exertion (RPE) was also increased (400g: ↑1.1 +/- 1.9RPE, 0.58, (-0.11 – 1.27), 500g: ↑1.1 +/- 2.3RPE, 0.58, (-0.26 – 1.42). There was no substantial change in heart rate (HR) in either gender. In conclusion, WRT makes substantial changes on male BL at heavier loads which may have implications for WRT training design. However, the females decreased speed and no change in BL mean its effectiveness as a training tool is still unclear from a physiological perspective. Study 2 investigated the benefits of utilising WRT during a swim-specific warm-up to improve 200m swimming performance. 10 national level female swimmers (age: 17.60 +/- 2.46, 200m personal best: 133.13 +/- 7.80) completed two performance trials 48 hours apart. Each trial consisted of a standard warm up (SWU) including 4x25m sprints either with or without WRT. Specific loads were determined for each participant with the intention of eliciting a PAP response. Following the SWU and 8-min recovery both groups commenced a 200m freestyle time trial (TT). BL, HR and RPE were collected prior to, and after, both the 4x25m sprints and 200m TT. Using WRT during the warm-up induced a PAP effect resulting in a possible increase of speed over the first 50m of -0.15 +/- 0.40 sec (↓0.5%; (-0.3-1.2)). However, it also reduced the time to fatigue resulting in a possible harmful effect to back-half speed with an increase of 0.53 +/-1.18sec (↑0.6%; (-1.6-0.2)) in the second 100m split. Therefore, the addition of WRT to induce a PAP response using an 8-min recovery period had no substantial effect on 200m TT performance with a trivial difference of 0.34 +/- 1.12sec (↑0.3%; 90% CI: (-0.2 – 0.7)). There was a small effect on BL and HR which could also indicate a PAP response to intervention. Our results showed that integrating a swim-specific PAP strategy, using WRT, to a SWU did not improve 200m swimming performance in elite female swimmers; however, did induce a PAP response and improved first 50m pace.
Keywords: Wearable resistance; Physiology; Swimming; Post-activation potentiation; Blood lactate; Freestyle; Performance